Strategi Pemasaran Digital dalam Mempertahankan Loyalitas Customer - Putri, Rezania Novianti; Fournawati, Sri Murdilah; Alamsyah, Alamsyah (Social Science Academic, 2023)
In this digital era, social media has become a trend in communication. The marketing trend in the world is shifting from conventional to digital. This digital marketing is more prospective because it allows potential customers to obtain all kinds of information about products and transact via the internet. as Sogo Supermal Karawaci does in selling products, the presence of Covid-19 has made companies aware of the importance of keeping up with the all digital era. The purpose of this research was to find out the marketing strategy by Sogo Supermal Karawaci in digital era via WhatsApp application, the name is WhatsApp Click&Shop in maintaining customer loyalty. The method used is a qualitative method by conducting direct interviews with Sogo employees and customers. Sogo always runs programs by giving vouchers with a certain mechanism to attract customers interest in buying products and to collaborate with certain banks. Sogo always tries to provide all conveniences and advantages to customers in buying and selling non-face to face to keep customers from continuing to shop at Sogo Supermal Karawaci amidst the many competitors in this digital era.